Indigenous Education, Mino-Bimaadiziwin, and the Fostering of Relational Space Through Indigenous Pedagogy - Hupfield, John (2015)
This paper examines the varying impacts of Indigenous pedagogy and formal schooling on the learning path of the author. It focuses on the historical context of residential schools, the Indian Control of Indian Education paper of 1972, and the shifting control of schools to Indigenous communities. With a resulting increase in Indigenous administration, staff, and curricula, the time is opportune for discourse on Indigenous pedagogy to come to the fore. The author utilizes personal relationships with mentors, learning experiences in and outside of schools, and the process of learning regalia construction to identify their contributions towards Anishinaabe mino-bimaadiziwin, the good life. The self-reflective examination documents their journey of coming to know Indigenous pedagogy as Anishinaabe.